Enhanced Photocatalytic Activity and Magnetic Properties of CoFe2O4/TiO2-Ag/S for Visible Light-Driven Photodegradation of Methylene Blue - Kunarti, Eko Sri; Agustiningsih, Dewi; Pambudi, Fajar Inggit; Syoufian, Akhmad; Santosa, Sri Juari (Indonesian Journal of Chemistry, 2025)
Environmental concerns drive the need for effective photocatalysts that can operate under visible light to degrade organic pollutants in wastewater. This study investigated TiO2-based photocatalyst doped with Ag and S to enhance its visible-light response, modified further with CoFe2O4 to introduce magnetic properties, resulting in a composite, CoFe2O4/TiO2-Ag/S. The synthesis was carried out by using cobalt nitrate hexahydrate and ferric nitrate nonahydrate for CoFe2O4 precursor, titanium tetraisopropoxide for TiO2 precursor, and silver nitrate with thiourea for Ag and S dopants. Results from characterization analyses, including FTIR, XRD, UV-vis, SEM-EDX, TEM, and VSM, confirmed the composite structure, with magnetic properties reflected in saturation magnetization of 10.69 emu g−1 and an extended UV-vis absorption edge indicating improved visible light activity. Photocatalytic tests for methylene blue degradation showed the highest performance (92%) with a 1:1 Ag:S ratio under visible light at pH 10 over 120 min, using 20 mg of catalyst in 5 ppm solution. Additionally, the composite demonstrated strong stability, retaining efficiency across six cycles of reuse.